Solvent Extraction of Phenolic Compounds and Determination Total Phenolic Content from Teucrium Polium Plant - Khudair, M. M.; Al-Ameri, S. A.H.; Abbas, S.; Najim, A.; Daba, K.; Abid, N.; Tarik, A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
A direct solvent extraction was used for the determination of phenolic compounds from Teucrium polium . Methanol, ethanol, iso-propanol, butanol and D.W  were used as an extractants and study  the affecting extraction factors including : the type and solvent concentration, temperature, extraction time and number of batch extraction, by  using Folin-ciocalteu method to determine the Total Phenolic Content (TPC) and measurement of the absorbance at Î»max 765nm. The accuracy and precision of this method were determined by preparing laboratory samples of Gallic acid , the results showed relative errors ranging from Â±0.5 â€“ 1.49 % and the standard deviation equal to 1.294 and the relative standard deviation did not exceed  0.71 %, the standard deviation of the mean was 0.647 and relative standard deviation of the mean was equal to 0.353% . The results showed that the  highest extraction  was obtained equals to  97% by methanol followed by ethanol and D.W., especially when the extraction takes place with 100% concentration , at 8 hr extraction time  at room temperature with two extraction batches.  This method was applied under the optimized experimental condition found in this work  for two Iraqi  local life samples from  Kut and Dehouk , the total phenolic content measurements were found to be equal to 183.250  and 236.991 mg/ g of dry Teucrium polium plant stem and 129.214 and 101.022 mg/g of dry Teucrium polium plant for Kut and Dehouk samples  respectively .